What is Internal Law of Religions?: An Approach Based on Wittgenstein’s Family Resemblances - Berkmann, Burkhard Josef (La pena nei diritti delle religioni, 2019)
The still emerging discipline of comparative religious law is faced with the task to define its object, which is the internal law of religions. What, for example, do Protestant church law, Islamic and Hindu law have in common? Prior attempts at a definition – e.g. those by Puza or Vanderlinden – do not completely satisfy. The author pursues a new path by elaborating a typological definition in the sense of Wittgenstein’s family resemblances. He lists a series of characteristics applicable to most religious laws, although not every religious law fulfils all of them. Examples are: revelation as a source of law, binding force only for the respective faithful, worship and doctrine of faith as matters to be regulated.